Age, Renal Dysfunction, Cardiovascular Disease, and Antihyperglycemic Treatment in Type 2 Diabetes Mellitus: Findings from the Renal Insufficiency and Cardiovascular Events Italian Multicenter Study. Issue 8 (26th July 2013) - Solini, Anna; Penno, Giuseppe; Bonora, Enzo; Fondelli, Cecilia; Orsi, Emanuela; Trevisan, Roberto; Vedovato, Monica; Cavalot, Franco; Cignarelli, Mauro; Morano, Susanna; Ferrannini, Ele; Pugliese, Giuseppe; et al.
<x xml:space="preserve">Abstract</x> Objectives To assess the distribution of antihyperglycemic treatments according to age and renal function and its relationship with cardiovascular disease in type 2 diabetes mellitus (T2DM). Design Cross‐sectional analysis. Setting Nineteen hospital‐based diabetes mellitus clinics in 2007 and 2008. Participants Fifteen thousand seven hundred thirty‐three individuals with T2DM from the Renal Insufficiency and Cardiovascular Events (RIACE) Italian Multicenter Study. Measurements Current antihyperglycemic treatments were recorded. Estimated glomerular filtration rate (eGFR) was calculated using the Chronic Kidney Disease Epidemiology Collaboration equation. Albuminuria was measured using immunonephelometry or immunoturbidimetry. Prevalence of major acute cardiovascular events was calculated according to age quartiles, treatments, and categories of eGFR (1 = ≥90; 2 = 60–89; 3 = 30–59; and 4 = <30 mL/min per 1.73 m2). Results Across age quartiles, eGFR declined progressively at a time‐linear rate, with an acceleration in older adults, whereas albuminuria increased; age and eGFR were associated with cardiovascular events independently of other confounders. With increasing age, percentage of participants using lifestyle treatments for their T2DM and taking metformin or glitazones fell; percentage taking sulphonylureas and repaglinide rose, and percentage taking insulin remained stable. In eGFR categories 3 and 4, use of metformin was 41.4% and 14.5%, respectively, and that of sulphonylureas was 34.2% and 18.1%, respectively. Inappropriate prescription of these agents, especially sulphonylureas, increased with age. Metformin was independently associated with lower prevalence of cardiovascular disease for any age quartile and eGFR category than all other treatments. Conclusion In real‐life conditions, use of agents that are not recommended in elderly adults with diabetes mellitus with moderate to severe renal impairment is frequent, but metformin is associated with lower cardiovascular event rates even in these individuals.